Stability of extruded diets for dogs - Lima, Daniele Cristina de; Bastos, Tais Silvino; Souza, Camilla Mariane Menezes; Silva, Juarez Ribeiro da; Oliveira, Simone Gisele de; Félix, Ananda Portella (Scientia Agraria Paranaensis, 2020)
Controlling the factors that influence the conservation of extruded dog foods can increase shelf life and/or guarantee the quality of shelf life of diets for these animals. Therefore, the objective was to evaluate the relationship among water activity (Aw), moisture (M), acidity, lipid peroxidation, crude protein (CP), ether extract (EE), and kibble size of extruded dog foods stored in sealed and open packages for 60 days (Experiment I). We also evaluated the stability of the Aw for up to 6.5 hours after coating with palatant (Experiment II). We manufactured four extruded dry dog foods: high CP and EE (HPE); low CP and EE (LPE); small kibble (SK); and large kibble (LK). In experiment I, the foods were stored in sealed 1 kg packages and 10 kg open packages, for a period of 60 days. We measured Aw, M, acidity, peroxide, CP, and EE of foods and the relative humidity (RH). Data were subjected to Pearson correlation analysis. For experiment II, samples were collected immediately after coating with palatant. Sub samples were collected every half hour to measure Aw. In experiment I, positive correlations were observed (P<0.05) among kibble size, M, and Aw; acidity, CP, EE, and M; and between Aw and RH, for open and sealed packages. There was also a positive correlation (P<0.05) for open packages among time, Aw, and peroxide. In experiment II, LK and LPE food presented Aw stabilized in less time. Diets with higher kibble size and high CP and EE levels are more unstable if kept in open packages. Extruded dry food with higher protein and lipid and smaller kibble size needs more time to stabilize its Aw.